1973
DOI: 10.1021/ja00790a049
|View full text |Cite
|
Sign up to set email alerts
|

Unsubstituted cyclopentadienyl cation, a ground-state triplet

Abstract: 13) Good Curie law behavior was observed for most samples down to liquid helium temperature. Although some showed deviations near 10°K, this was related to the prior history of the sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
0
6

Year Published

1975
1975
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(104 citation statements)
references
References 0 publications
8
88
0
6
Order By: Relevance
“…[33] Finally, we prepared cyclopentadienyl cation 22 itself, in collaboration with Martin Saunders and Mike McBride at Yale. [34] It was prepared from 5-bromocyclopentadiene and a very strong Lewis acid under special conditions. It also showed the ESR spectrum of a triplet, and the temperature effects of a groundstate triplet.…”
Section: Aromaticitymentioning
confidence: 99%
“…[33] Finally, we prepared cyclopentadienyl cation 22 itself, in collaboration with Martin Saunders and Mike McBride at Yale. [34] It was prepared from 5-bromocyclopentadiene and a very strong Lewis acid under special conditions. It also showed the ESR spectrum of a triplet, and the temperature effects of a groundstate triplet.…”
Section: Aromaticitymentioning
confidence: 99%
“…Baird [14] argued in a classic paper, however, that aromaticity should also be associated with 4n p-electron monocycles in their triplet states. This argument, based on qualitative calculation of comparative energetics, is supported by the existence of planar triplet ground states of 4p species such as C 5 X Cl [15,16]). An extensive ab initio study by Gogonea et al [17] concluded that triplet aromaticity in 4n p systems does indeed exist and that is associated with planarisation, bond equalisation, stabilisation, negative NICS, downfield 1 H NMR shifts, and significant diamagnetic orbital susceptibility.…”
Section: Introductionmentioning
confidence: 98%
“…[50] X X-Bandensystems in beiden Molekülen als eine schwache (mit dem Symbol "j = 0" gekennzeichnete) Linie beobachtet, der sich unmittelbar eine we- …”
Section: Cyclopentadienylkationunclassified